RENEWABLE STOCK PRICE MODEL SEBAGAI PENDUKUNG INVESTASI SAHAM: STUDI KASUS SAHAM JII - Evita Purnaningrum (STIE DWI SAKTI BATURAJA, 2018)
Stock investors want accurate and fast stock price estimates. Until now, the stock price prediction or estimation still uses different models for different stocks. This is less effective if we want to predict all stocks on a stock index. Renewable Stock Price Model is an estimate of stock prices that combines mathematical models, namely Geometric Brownian Motion (GBM) with Kalman filters. This model is able to estimate all stocks on one index in this case JII. This is evidenced by the estimated level of accuracy of 96.04%. Therefore, this method answers investor anxiety in making stock investment decisions in one index. The estimated difference in return and real shares is 23 rupiah in May 2017.